Loss of endoplasmic reticulum calcium pump expression in choroid plexus tumours. Issue 6 (October 2014) - Ait‐Ghezali, Lamia; Arbabian, Atousa; Jeibmann, Astrid; Hasselblatt, Martin; Hallaert, Giorgio G.; Van den Broecke, Caroline; Gray, Françoise; Brouland, Jean‐Philippe; Varin‐Blank, Nadine; Papp, Bela
<x xml:space="preserve">Abstract</x> Aims Sarco/Endoplasmic Reticulum Calcium ATPase‐type calcium pumps (SERCA enzymes) control cell activation by sequestering calcium ions from the cytosol into the endoplasmic reticulum. Although endoplasmic reticulum calcium signalling plays an important role in the regulation of choroid plexus epithelial function, SERCA expression in the choroid plexus has not been investigated so far. Methods In this work we investigated the expression of the SERCA3‐type calcium pump in choroid plexus epithelial cells grown in vitro, and in normal and hyperplastic choroid plexus tissue, in choroid plexus papillomas displaying various degrees of atypia, and in choroid plexus carcinoma by immunohistochemistry in situ. Results Whereas normal choroid plexus epithelial cells express SERCA3 abundantly, SERCA3 expression is strongly decreased in papillomas, and is absent in choroid plexus carcinoma, while expression in hyperplastic epithelium is high, similarly to normal epithelium. SERCA3 expression was detected also in normal primary choroid plexus epithelial cells grown in vitro, and expression was markedly enhanced by short‐chain fatty acid‐type cell differentiation inducing agents, including valproate. Conclusion These observations show that SERCA3 is a new phenotypic marker of normal choroid plexus epithelial differentiation, and that SERCA3 constitutes an early tumour marker 'by loss of expression' in the choroid plexus that may be useful to distinguish hyperplastic processes from papillomas. Endoplasmic reticulum calcium homeostasis becomes anomalous, due to loss of SERCA3 expression, already in benign neoplastic lesions of the choroid plexus epithelium.